Comprehensive comparison of industrial cannabinoid extraction techniques: Evaluation of the most relevant patents and studies at pilot scale - López-Olmos, Cristina; García-Valverde, María Teresa; Hidalgo, Jesús; Ferrerio-Vera, Carlos; Sánchez de Medina, Verónica (Frontiers in Natural Products, 2022)
Cannabinoids are gaining attention in many sectors, including the pharmaceutical, nutraceutical, and cosmetic sectors. To date, several conventional and alternative techniques have been applied for Cannabis sativa L (C. sativa L.) extraction at the industrial scale. The conventional methods are liquid solvent extraction, including polar and non-polar solvents such as ethanol, hexane, petroleum ether, and other solvent extraction. Pressurized gas extraction is another conventional method and comprises gaseous hydrocarbon extraction such as n-butane and n-propane, supercritical or subcritical carbon dioxide extraction, and extraction using a refrigerant gas such as 1,1,1,2-tetrafluoroethane (HFC 134a). Alternative extraction methods include microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), hydrodynamic cavitation, and pulsed electric fields (PEF). This review thoroughly analyzes and compares the main extraction techniques and technologies at the industrial scale found in the patent literature. In addition, several aspects of the pretreatment of cannabis plant material and its influence on extraction are also discussed.